Analysis of Multiple-Choice Items in Physical Education Subject: A Systematic Literature Review - Muhammad alif al haqqi; Muhammad Sazeli Rifki; Arsil Arsil; Sepriadi Sepriadi (STKIP Singkawang, 2025)
This systematic literature review aims to analyze the characteristics and quality of multiple-choice items used in assessments within the field of Physical Education, Sports, and Health. The study seeks to identify common trends, strengths, and weaknesses in the formulation and effectiveness of multiple-choice questions in evaluating students' knowledge and understanding of Physical Education, Sports, and Health concepts. A systematic literature review approach was employed, focusing on peer-reviewed journal articles and academic sources published within the last decade. Studies were selected based on their relevance to multiple-choice question analysis in Physical Education, Sports, and Health assessments. The review examined aspects such as question validity, reliability, alignment with learning objectives, and cognitive level distribution. The analysis revealed several key findings regarding multiple-choice question construction in Physical Education, Sports, and Health assessments. Common issues include ambiguity in question wording, misalignment with curriculum objectives, and inadequate assessment of higher-order thinking skills. However, well-constructed multiple-choice questions were found to align effectively with learning goals, incorporate well-designed answer choices, and assess both lower-order and higher-order cognitive skills.The findings indicate that while multiple-choice questions remain a dominant assessment method in Physical Education, Sports, and Health, improvements are necessary to enhance their effectiveness. Recommendations include adopting standardized guidelines for question development, providing training for educators on multiple-choice question construction, and exploring alternative assessment formats to better evaluate students' comprehensive understanding of Physical Education, Sports, and Health concepts.